A study of public awareness on sport personal accident insurance in Kompleks Sukan Negara, Bukit Jalil, Kuala Lumpur / Akmal Afiq Kamarolzaman - Kamarolzaman, Akmal Afiq (Faculty of Business and Management, 2010)
This research is conduct to carry out “Public awareness on sport personal accident insurance in Kompleks Sukan Negara, Bukit Jalil, Kuala Lumpur”. The main objective is to measure and identify the most factors that contribute to the awareness of public towards sport personal accident insurance. It consist of three factor that are barrier that influence public to buy / demographic trends which describe income and lifestyle of public toward this product / critical role of media towards this product. At this research probability sampling technique and simple random sampling techniques were been used to get data that are require. Population of the research was publics that using amenities at Kompleks Sukan Negara, Bukit Jalil, Kuala Lumpur. About 50 respondents were getting from the research to help for accomplish this research by answering questionnaires that distributes to them. All data collected were analyzed systematically by Statistical Package for Social Science (SPSS) the conclusion of this study was the outcome from the data and analysis which include the answer to the research question and research objective. , The recommendation shows the way to overcome problem or develop new ways to strengthen the awareness among public.